Presentation is loading. Please wait.

Presentation is loading. Please wait.

Recursive Definitions Rosen, 3.4. Recursive (or inductive) Definitions Sometimes easier to define an object in terms of itself. This process is called.

Similar presentations


Presentation on theme: "Recursive Definitions Rosen, 3.4. Recursive (or inductive) Definitions Sometimes easier to define an object in terms of itself. This process is called."— Presentation transcript:

1 Recursive Definitions Rosen, 3.4

2 Recursive (or inductive) Definitions Sometimes easier to define an object in terms of itself. This process is called recursion. –Sequences {s 0,s 1,s 2, …} defined by s 0 = a and s n = 2s n-1 + b for constants a and b and n  Z+ –Sets 3  S and x+y  S if x  S and y  S –Functions Example: f(n) = 2 n, f(n) = 2f(n-1) and f(0) = 1

3 Recursively Defined Functions To define a function with the set of nonnegative integers as its domain 1.Specify the value of the function at zero (or sometimes, it first k terms). 2.Give a rule for finding its value at an integer from its values at smaller integers.

4 Examples of Recursively Defined Functions Factorial Function n!  n! = n(n-1)(n-2)….(1)  f(0) = 1, f(n) = n(f(n-1)) a n  f(0) = 1, f(n+1) = f(n)*a Fibonacci Numbers  f 0 =0, f 1 =1, f n+1 = f n + f n-1  {0,1,1,2,3,5,8,13,...}

5 Prove that the nth term in the Fibonacci sequence iswhen n  2 Induction Proof: Basic Step: Let n = 2, then f 2 = 1 = =1+0 Inductive Step: Consider k  2 and assume that the expression is true for 2  n  k. We must show that the expression is true for n = k+1, i.e., that f k+1 f k+1 = f k +f k-1 by definition by the inductive hypothesis

6 Fibonacci Proof (cont.) Since f 2 is true and [f n is true for 2  n  k  f k+1 ] is true, then f n is true for all positive integers n  2.

7 Recursively Defined Set Example Let the set S be defined recursively as 3  S and x+y  S if x  S and y  S. Prove that S is equal to the set of positive integers divisible by 3 (set A). Proof: To show that S = A, we must show that A  S and that S  A.

8 Recursive Set Example (cont.) First we will show that A  S. To do this we must show that every positive integer divisible by 3 is in S. This is the same as saying that 3n is in S for n  Z+. We will do an inductive proof. Let p(n) be the statement that 3n  S for n a positive integer. Basis Step: p(1) = 3(1) = 3 Inductive Step: We will show that p(n)  p(n+1) Let p(n)  S. Then p(n+1) = 3(n+1) = 3n + 3. Since 3n  S and 3  S, then 3n+3  S. Therefore every element in A must be in S.

9 Recursive Set Example (cont.) Now we will show that S  A. To do this we must show that every element in S is divisible by 3, i.e., that it can be represented as 3(j) where j is a positive integer. Basis Step: 3  A since 3 = 3(1) Inductive Step: Assume x,y are in A (where x,y  S). x and y are divisible by 3 since they are both in A. Therefore x = 3j and y = 3k for j,k  Z+. Then z = x+y = 3j+3k = 3(j+k), which is divisible by 3, so z  A (and by definition, z  S). Therefore every element in S must be in A

10 Prove f n >  n-2 where  = (1+  5)/2 whenever n  3 Inductive Proof Basis Step: First we will show f n >  n-2 for f 3 and f 4.  3-2 =  1 = (1+  5)/2 < (1+  9)/2 = 4/2 = 2 = f 3  4-2 =  2 = [(1+  5)/2] 2 = (1+ 2  5 + 5)/4 = (6+ 2  5)/4 = 3/2 +  5/2 < 3/2 +  9/2 = 3 = f 4

11 f n >  n-2 (cont.) Inductive Step: Assume that f k >  k-2 is true for all nonnegative integers 3  k  n when n>4. We must show that f n+1 >  n-1. Lemma:  2 = [(1+  5)/2] 2 = (1+2  5 +5)/4 = 3/2 + (  5)/2 = 1 + (1+  5)/2 = 1+ 

12 f n >  n-2 (cont.)  n-1 =  2  n-3 = (  +1)(  n-3 ) =  n-2 +  n-3 By our inductive hypothesis f n-1 >  n-3 and f n >  n-2 f n+1 = f n + f n-1 >  n-2 +  n-3 =  n-1 Since f 3 is true and [f k is true for 3  k  n]  f n+1 is true, then f n is true for all positive integers n  3.

13 Find a closed form solution to the recursive equation: T(n) = T(n-1) + c 1. T(0) = c 0 One approach is to write down several terms, guess what the equation is, and then prove that your guess is correct (or not) using an induction proof. T(0) = c 0 T(1) = T(0) + c 1 = c 0 + c 1 T(2) = T(1) + c 1 = c 0 + 2c 1 T(3) = T(2) + c 1 = c 0 + 3c 1 T(4) = T(3) + c 1 = c 0 + 4c 1 Guess that T(n) = c 0 + nc 1

14 Induction proof Basis Step: for n = 0, T(0) = c 0 + (0)c 1 = c 0 Inductive Step: Assume that T(n) = c 0 + nc 1, we must show that T(n+1) = c 0 + (n+1)c 1. T(n+1) = T(n) + c 1 = c 0 + nc 1 + c 1 = c 0 + (n+1)c 1.

15 Find a closed form solution to T(1) = c 0, T(n) = 2T(n-1)+c 1 T(1) = c 0 T(2) = 2T(1) + c 1 = 2c 0 + c 1 T(3) = 2T(2)+c 1 = 2(2c 0 +c 1 )+c 1 = 4c 0 +3c 1 T(4) = 2T(3)+c 1 = 2(4c 0 +3c 1 )+c 1 = 8c 0 +7c 1 T(5) = 2T(4)+c 1 = 2(8c 0 +7c 1 )+c 1 = 16c 0 +15c 1 Guess that T(n) = 2 n-1 c 0 + (2 n-1 -1)c 1

16 Prove that T(1) = c 0, T(n) = 2T(n-1)+c 1 has closed form solution T(n) = 2 n-1 c 0 + (2 n-1 -1)c 1 Basis Step: T(1) = 2 1-1 c 0 + (2 1-1 -1)c 1 = c 0 Induction Step: Assume that T(n) = 2 n-1 c 0 + (2 n-1 -1)c 1. We must show that T(n+1) = 2 (n+1)-1 c 0 + (2 (n+1)-1 -1)c 1 = 2 n c 0 + (2 n -1)c 1. T(n+1) = 2T(n) + c 1 = 2[2 n-1 c 0 + (2 n-1 -1)c 1 ]+ c 1 = 2 n c 0 + (2 n -2)c 1 + c 1 = 2 n c 0 + 2 n c 1 - c 1 = 2 n c 0 + (2 n -1)c 1.


Download ppt "Recursive Definitions Rosen, 3.4. Recursive (or inductive) Definitions Sometimes easier to define an object in terms of itself. This process is called."

Similar presentations


Ads by Google